Influence of Digital Marketing, Location, Product Quality, and Product Price on Purchase Decisions in Food and Beverage Companies: A Systematic Literature Review - Tooy, Yohanes L.; Melviana; Persius, Angel Andromeda; Tinambunan, Michael; Tanuwijaya, Terrance; Mulyandi, Muhammad Rachman; kalfin (International Journal of Humanities, Law, and Politics, 2024)
In the increasingly fierce business competition, companies need to understand the factors that influence purchasing decisions. These factors can be digital marketing, location, product quality, and product price. Therefore, this study aims to determine the effect of digital marketing, location, product quality and product prices on food and beverage companies based on literature review. In this study, the data used are articles published on Google Schoolar from 2013-2023. This study uses a systematic literature review method in obtaining results based on research objectives. From the research results obtained that digital marketing at this time has a very important role in influencing purchasing decisions. Furthermore, location also has an important role in influencing purchasing decisions. Strategic locations are easier for customers to reach so that buyer interest will be greater. In addition, high product quality also influences purchasing decisions. If the product quality is high, consumers will buy more of these products because they meet the needs and expectations of the buyers. Prices that match the value of the product will be purchased more by consumers. Based on these results, it is hoped that it can provide an overview to food and beverage companies in determining company purchasing decisions